The quality of customer service in the retention and loyalty of service companies - Zapata Caraguay, Leonela Estefanía; Ocaña Rogel, Madeleine Lizeth; Feijoo Jaramillo, Irene María; Guerrero Carrasco, Martha Jaroslava; Sarmiento Chugcho, Carlos Bolívar (Revista Universidad de Guayaquil, 2025)
The research analyzes how incentives, brand commitment, and brand loyalty affect Internet companies in Machala, Ecuador. Excellent service is crucial for customer satisfaction and loyalty, especially in a competitive environment. The aim is to determine how incentives influence customer loyalty and commitment by evaluating their impact on perceived brand value and the formation of lasting associations. The study used a questionnaire based on scales to understand the opinions of 384 users of online services in Machala. Variables such as incentives, loyalty, and commitment were examined through a structural analysis illustration (AE), assessing the consistency and legitimacy of the concepts. The study found that incentives strongly affect loyalty (β = 0.81) and customer commitment (β = 0.49). Commitment also positively influences loyalty (β = 0.42). Clearly communicating the benefits and additional advantages is essential for retaining customers. Incentives are fundamental for fostering customer loyalty and commitment. Organizations should focus on methods that enhance service excellence and provide personalized interactions.